Assessment of Aqueous Leaf Extracts of Parthenium Hysterophorus L. On Seedlings Growth of Wheat (Journal of Bio-Science, 2023)
An investigation was conducted to assess the effect of Parthenium hysterophorus L. leaf extracts on seedling growth of three wheat (Triticum aestivum L.) varieties viz. Sourav, BARI Gom 22 and BARI Gom 33. It was observed that the growth of wheat seedlings was significantly influenced by the Parthenium extract treatments. BARI Gom 22 showed more tolerance to Parthenium treatments than BARI Gom 33 and Sourav. Generally, wheat seedlings growth was inhibited by Parthenium extract treatments at all periods. The percent inhibition of shoot and root elongation were more visible at 5% treatment concentration at all periods than other extract treatments. On the other hand the number of root of wheat seedlings was not found to be affected by Parthenium at 7 and 10-day periods.  It was also noted that the effect of Parthenium extracts on wheat seedling growth is concentrations dependent manner.J. Bio-Sci. 31(1): 61-70, 2023